The Economics of adjustment and growth - Agenor, Pierre-Richard (San Diegro Academic Press, 2000)
This book provides an excellent review of the policy issues confronting developing economice. It covers both the short- run macroeconomic management and structural adjustment policies aimed at economic growth. It provides a rigorous, and accessble blendin
Keywords: Economic development; Monetary policy; Economic policy; Saving and investment